2020
DOI: 10.4314/ejhs.v30i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Burden, Types and Associated Risk Factors among Kenyan Human Immunodeficiency Virus-1 and Mycobacterium Tuberculosis Co-infected Injection Substance UsersAnemia Burden, Types and Associated Risk Factors among Kenyan Human Immunodeficiency Virus-1 a

Abstract: BACKGROUND፡ Although injection substance users and individuals co-infected with Human Immunodeficiency Virus-1 and Mycobacterium tuberculosis suffer marked hematologic derangements, the rates, levels, morphologic types and associated risk factors of anemia among Human immunodeficiency virus and Mycobacterium tuberculosis coinfected injection substance users has not been reported in Kenya.METHODS: This cross-sectional study determined anemia rates, levels and morphologic types. Anemia was associated with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Pulmonary TB is usually treated with isoniazid and rifampicin ( 28 ). Only 19 (25.3%, 4.5-9.6 CI) of 75 initial MTB diagnoses had MTB in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary TB is usually treated with isoniazid and rifampicin ( 28 ). Only 19 (25.3%, 4.5-9.6 CI) of 75 initial MTB diagnoses had MTB in this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies have reported variations in morphological types of anemia. In a study in Nigeria, Esan et al reported a normochromic normocytic type of anemia as a major type of anemia in HIV patients, 13 and in Kenya, microcytic hypochromic anemia was the commonest type of anemia, followed by normocytic hypochromic anemia, 14 while in another similar study in Kenya, hypochromic and normochromic anemia were the commonest. 15 In Tanzania, Makubi et al reported microcytic anemia as the most predominant morphological type of anemia, 16 while in Uganda, 17 microcytic hypochromic anemia was reported as the commonest type of anemia.…”
Section: Introductionmentioning
confidence: 95%
“…Further study also revealed that HIV Patients were older age, female sex, hepatitis C virus coinfection, higher virial load, 1c ART treatment, illicit drug and BMI < 18.5 kg/m 2 were associated with low hemoglobin level; on the contrary BMI between 25 to < 30 kg/m 2 or BMI ≥ 30 kg/m 2 , smoker and alcohol addicted were associated with higher hemoglobin level overtime [ 26 ]. Other study indicated that, weight, CD4 cells < 350/mm 3 [ 27 ], tuberculosis co-infection, advanced WHO stage [ 28 ], other opportunistic infections, having poor adherence to ART, rural residence, and eating non-diversified foods were significantly associated with low hemoglobin level [ 29 ].…”
Section: Introductionmentioning
confidence: 99%